2022
DOI: 10.3390/su141811223
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Participative Leadership in Empowerment and Resident Participation

Abstract: Traditional tourism development has adopted a top-down approach, and the role of government has primarily been decision making and regulation in regard to tourism development. There has been growing interest in residents’ participation in tourism destination development and management. The study aims provide empirical evidence by examining the relationship between participative leadership, empowerment, and tourism participation among residents living in the provinces near the borders in Korea. We examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the previous literature, it was identified that when residents perceive benefits from tourism, they are more willing to be empowered to support tourism for their communities [28]. In previous studies, the different effects of multiple empowerments were shown, and empirical studies regarding empowerment and residents' action were called for [8,28]. Specifically, Nunkoo and So [58] examined several antecedents of residents' support.…”
Section: Resident Support For Tourismmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous literature, it was identified that when residents perceive benefits from tourism, they are more willing to be empowered to support tourism for their communities [28]. In previous studies, the different effects of multiple empowerments were shown, and empirical studies regarding empowerment and residents' action were called for [8,28]. Specifically, Nunkoo and So [58] examined several antecedents of residents' support.…”
Section: Resident Support For Tourismmentioning
confidence: 99%
“…Previous research regarding DMZ areas and tourism has been explored in various perspectives such as the motivation of dark tourism [3], the economic values of wellpreserved natural environments [4,5], border images and visual representations [6], and the role of tourism as a peaceful connection between North and South Korea [7]. Recently, relevant stakeholders' behaviors in DMZ areas have been studied [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research also focuses on the role of various stakeholders around DMZ areas for tourism and the decision-making process for tourism development [53,54]. Specifically, Kim, Choe, and Lee [50] investigated residents' support for DMZ visits during pre-and post-development stages.…”
Section: Dmz Tourismmentioning
confidence: 99%
“…We argue that this impact has both potential and the ability to be a challenge for participating in this program. On the one hand, the role of government-related participants helps to promote their households' participation, or people are motivated by participative leadership [58]. On the other hand, this also reveals unsustainability when incentives for community participation are influenced by some individuals in the government system.…”
Section: Participation Levels Of People In the Ntp For New Rural Deve...mentioning
confidence: 99%